Toddlers' Use of Grammatical and Social Cues to Learn Novel Words. Issue 3 (2nd July 2016) - Paquette-Smith, Melissa; Johnson, Elizabeth K.
ABSTRACT: By their second birthday, children have begun using grammatical cues to decipher the meaning of newly encountered words. By 3 years of age, there is evidence that children are more reliant on grammatical than social cues to decipher verb meaning (Nappa, Wessel, McEldoon, Gleitman, & Trueswell, 2009). Here, we investigate children's reliance on grammatical and social information to infer the meaning of a novel noun. First we investigate the emergence of children's use of grammatical number markings to infer noun meaning. Then we explore how children integrate this cue with other (social) cues to word meaning. In Experiment 1, we demonstrate that children begin using grammatical number markings to resolve referential ambiguity by 24 months of age. In Experiment 2, we pit the grammatical number cue against a well-established social cue and find that 2-year-olds' reliance on grammatical number markings is already strong enough to compete with social eye gaze cues.